Investigating the effectiveness of quizizz among the secondary school students' formal emails writing - Vannessa, Jonathan (2024)
This research investigates the effectiveness of quizizz among the secondary school students' formal emails writing. A total of Student A to Student Z form 4 students with average to high proficiency participated in the study, which spanned four weeks and involved both pre-test and post-test of email writing. Initially, the participants completed a pre-test consisting of one email writing question from Kedah SPM Trial Paper 10. Then, four students were selected for a group interview to hear their understanding of email writing preparation. Following the interview, students engaged in a two-week intervention covering key sections of content, communicative achievement, organization, and language. After the intervention, students were evaluated through a grammar test using Quizizz, an interactive online learning platform. The results demonstrated a significant improvement in email writing skills among students. Additionally, interviews conducted with four participants highlighted a strong preference for gamified learning approaches, revealing insights into their motivational drives. This study suggests that incorporating gamified learning strategies can effectively enhance grammar acquisition and student engagement which are asked after the post-test on the fourth week. Future research should expand the sample size and explore further elements of online teaching, given the expansive potential of this educational approach. Overall, the findings affirm the hypothesis that gamified learning positively impacts ESL students’ email writing learning outcomes and motivation.